Implementation of Enterprise Resource Planning (ERP) Systems in Organizations Since Coevolution (2018)
Introduction: The literature review article derives from the research “Implementation of enterprise resource planning (ERP) systems in organizations since coevolution” conducted in 2016 and 2017 at the School of Industrial Engineering, Universidad Distrital Francisco José de Caldas.Problem: According to various research papers, ERP implementations have failed and generate business losses.Aim: To design a study proposal for the successful implementation of ERP in organizations.Methods: We started from a review of the literature related to ERP implementation of in organizations and identified that 70 % of companies did not obtain the expected results. It is argued that erp adoption can be understood as a coevolutionary process based on the interaction among employees through formal and informal affiliation networks.Results: It is proposed that individuals who have the greatest potential to influence others are identified in order to initiate an information dissemination process that flows from the most influential nodes to those with which they interact.Conclusion: The understanding of change as a coevolution process in formal and informal networks provides an opportunity to discuss and rethink the way in which companies are organized.Originality: To date, the implementation of this type of platform has not been addressed from this point of view.Limitations: The proposal is in the conceptual phase, but there is still no empirical research that allows its validation.